Peer Support as a Novel Strategy to Mitigate Post‐Intensive Care Syndrome. (April 2016) - Mikkelsen, Mark E.; Jackson, James C.; Hopkins, Ramona O.; Thompson, Carol; Andrews, Adair; Netzer, Giora; Bates, Dina M.; Bunnell, Aaron E.; Christie, LeeAnn M.; Greenberg, Steven B.; Lamas, Daniela J.; Sevin, Carla M.; et al.
Abstract : ABSTRACT : Post‐intensive care syndrome, a condition defined by new or worsening impairment in cognition, mental health, and physical function after critical illness, has emerged in the past decade as a common and life‐altering consequence of critical illness. New strategies are urgently needed to mitigate the risk of neuropsychological and functional impairment common after critical illness and to prepare and support survivors on their road toward recovery. The present state of critical care survivorship is described, and postdischarge care delivery in the United States and the potential impact of the present‐day fragmented model of care delivery are detailed. A novel strategy that uses peer support groups could more effectively meet the needs of survivors of critical illness and mitigate post‐intensive care syndrome.